Smart Mesoporous Silica Nanocapsules as Environmentally Friendly Anticorrosive Pigments. (15th September 2015) - Zea, C.; Barranco-García, R.; Chico, B.; Díaz, I.; Morcillo, M.; de la Fuente, D.
Abstract : Nowadays there is a special interest to study and develop new smart anticorrosive pigments in order to increase the protection life time of organic coatings and, simultaneously, to find alternatives to conventional toxic and carcinogenic hexavalent chromium compounds. In this respect, the great development of nanotechnologies in recent years has opened up a range of possibilities in the field of anticorrosive paints through the integration of encapsulated nanoscale containers loaded with active components into coatings. By means of a suitable design of the capsule, the release of the encapsulated corrosion inhibitor can be triggered by different external or internal factors (pH change, mechanical damage, etc.) thus preventing spontaneous leakage of the active component and achieving more efficient and economical use of the inhibitor, which is only released upon demand in the affected area. In the present work, the improved anticorrosive behaviour achieved by encapsulated mesoporous silica nanocontainers filled with an environmentally friendly corrosion inhibitor has been evaluated. It has been proven that a change in the pH allows the rupture of the capsules, the release of the inhibitor, and the successful protection of the carbon steel substrate.